Helminths Found in Subtropical Plants Growing in Uzbekistan - Bolliyev Asliddin Tursunmamatovich (American Journal of Biology and Natural Sciences, 2025)
This article studies helminths common in subtropical plants growing in Uzbekistan. Subtropical plants such as citrus, figs, pomegranates and dates serve as a breeding ground for various helminths that can affect their health and productivity. The study examines the species composition, ecological characteristics and impact of these helminths on plant development.